External Debt - Blessing or Curse: Empirical Evidence from Pakistan - ud-Din, Minhaj; Khan, Muhammad Azam; Tariq, Muhammad (International Journal of Economics and Financial Issues, 2020)
This study investigates the impact of external debt on the economic growth of Pakistan using annual time series data over the period 1976 to 2018. For this purpose, the syntheses of debt overhang and debt crowding-out hypotheses are examined within the framework of augmented Solow growth model. An autoregressive distributed lag (ARDL) model, Error Correction model and appropriate data diagnostic tests are applied. The empirical results indicate that external borrowing and debt servicing hamper the economic growth in Pakistan. Results reveal that 1% increase in stock of external debt is causing 0.20% fall in economic growth. Similarly,1% increase in debt servicing is causing 0.13% fall in economic growth. The findings of this study suggest that the policy makers should create a conductive environment for bringing increase in the level of domestic savings and exports, and should focus on increasing the inflow of capital through foreign direct investment and attracting the foreign exchange reserves. Incorporation of debt monitoring system along with its management is also required for minimizing the adverse effects of debt overhang and debt crowding out effects of the external debt. Keywords: External Debt; Economic Growth; ARDL; Pakistan JEL Classifications: F34, O11, C22, P24 DOI: https://doi.org/10.32479/ijefi.10134